Upaya Meningkatan Hasil Belajar Siswa Melalui Strategi Pembelajaran Peer Lessons Dalam Mata Pelajaran Fiqih Siswa Kelas VIII MTS Jamiyah Mahmudiyyah - Syarifah Mutia Rahmi, Muhammad Saleh, Muammar Al-Qadri (Pusdikra-Publishing.com, 2021)
Study fiqh in class VIII students at MTs. Jam'iyah mahmudiyanag Tanjung Pura 2) low student learning outcomes that have not been completed 3) the right learning strategy has not been found: The objectives of this research are: to determine student learning outcomes in Fiqh subjects with alms, grants, and gifts at MTs Jam 'iyah Mahmudiyah Tanjung Pura before and after using the peer lessons learning strategy. This research was conducted in the form of classroom action research, in accordance with the chosen research, namely classroom action research, this research is an action research model in the form of spiritual and one cycle to the next cycle. can improve student learning outcomes. The results of student learning before using the peer lessons strategy have not met the minimum standard of completeness criteria (KKM) However, applied after the peer lesson strategy in the learning process, student learning outcomes have increased. Compared to student learning outcomes in the pre-test. In the first cycle, student learning outcomes increased only after the second cycle was implemented. And this means that the Peer Lessons protection strategy is effective for use in learning to improve student learning outcomes.